2021
DOI: 10.1186/s12967-021-02790-w
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of steroid resistance and steroid dependence in nephrotic syndrome children

Abstract: Background Steroid resistant (SR) nephrotic syndrome (NS) affects up to 30% of children and is responsible for fast progression to end stage renal disease. Currently there is no early prognostic marker of SR and studied candidate variants and parameters differ highly between distinct ethnic cohorts. Methods Here, we analyzed 11polymorphic variants, 6 mutations, SOCS3 promoter methylation and biochemical parameters as prognostic markers in a group o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 55 publications
0
12
0
1
Order By: Relevance
“…Recently, growing studies focus on the association between MIF -794 CATT 5−8 or -173 G>C polymorphism and INS susceptibility as well as steroid treatment response. At present, a total of two studies investigated the association between MIF -794 CATT 5−8 polymorphism and INS, and both reported that a higher CATT number was not associated with increased risk of INS and steroid resistance (3,6). However, studies related to the association between MIF -173 G>C polymorphism and INS presented conflicting results, so we conducted a meta-analysis to clarify the association between the MIF -173 G>C polymorphism and INS.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recently, growing studies focus on the association between MIF -794 CATT 5−8 or -173 G>C polymorphism and INS susceptibility as well as steroid treatment response. At present, a total of two studies investigated the association between MIF -794 CATT 5−8 polymorphism and INS, and both reported that a higher CATT number was not associated with increased risk of INS and steroid resistance (3,6). However, studies related to the association between MIF -173 G>C polymorphism and INS presented conflicting results, so we conducted a meta-analysis to clarify the association between the MIF -173 G>C polymorphism and INS.…”
Section: Introductionmentioning
confidence: 97%
“…The exact pathogenesis of INS and the precise mechanism of the difference in steroid response remain unknown. Current evidence indicates that genetic polymorphisms can affect INS susceptibility and predict steroid treatment response (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a literature review of different gene variations related to steroid therapy response resulted in discordant conclusions. Not only cytokine genes, but also steroid-metabolism-related genes, displayed contradictory results in various ethnic groups [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Steroid-resistant nephrotic syndrome is not a single entity [4]. Different factors discussed in term of steroid-resistance formation, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Different factors discussed in term of steroid-resistance formation, i.e. pathomorphological type of disease (the most dominant lesion is focal segmental glomerulosclerosis (FSGS) [4,5], genetic markers [6], metabolic factors [7].…”
Section: Introductionmentioning
confidence: 99%